FIXED POINT THEOREMS IN PARTIAL b-METRIC-LIKE SPACES - Arunchai, A.; Ngeonkam, B. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2021)
In this paper, we introduce an interesting extension of the b-metric space called b-metric-like space. We investigate some contraction mapping in partial b-metric-like space and prove the existence of fixed point of this mapping in partial b-metric-like space under some conditions.